Prospective Genomic Profiling Study in Sarcoma Patients - Ho, Gwo Fuang; Cheong, E Von; Chye, Wei Ying; Mun, Kein Seong; Malik, Rozita Abdul; Saad, Marniza (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Sarcoma is a heterogenous group of malignancy with diverse pathology and clinical behavior. Survival rates differ among histological subtypes, but overall prognosis remains poor due to the scarcity of effective systemic therapies. An insight into the genomic characteristics of different sarcoma histological subtypes enhances our understanding of the disease and highlights potential targeted therapies.Objective We aim to enhance our understanding on the genomic profile of sarcomas and identify actionable genetic variants with the associated targeted therapies.Materials and Methods A prospective tumor genomic profiling study was conducted via next-generation sequencing, involving 30 patients with a diagnosis of soft tissue or bone sarcoma at the University of Malaya Medical Centre. We evaluated the frequency and types of genomic aberrations and identified genomic variants with a therapeutic target.Results A total of 70 genetic mutations were identified. The most frequently involved genes were TP53 (30.0%), followed by RB1 (20.0%), PIK3CA (10.0%), KIT (10.0%), PDGFR-α (10.0%), CKS1B (10.0%), KDR (10.0%), and MCL1 (10.0%). Genomic alteration involving the ALK gene was the only actionable variant identified. The DCTN1–ALK fusion was found to be targetable using entrectinib.Conclusion Although the number of actionable variants identified was limited, such data are crucial for the selection of patients into clinical trials on novel therapies in the future and for establishing prognostic biomarkers.
Keywords: sarcoma; genomics; mutation; entrectinib